TESTING OF PECKING ORDER THEORY THROUGH THE RELATIONSHIP: EARNINGS, CAPITAL STRUCTURE, DIVIDEND POLICY, AND FIRMS VALUE - Harmono Harmono (Jurnal Keuangan dan Perbankan, 2012)
This study aimed to test the pecking order theory through its correlation among earnings dimension, capitalstructure, dividend policy and firms value perspective. By loading the correlation between dimension one toanother, it indicated that management behavior tended to retained earnings accumulation or to debt collectionin financing the operation of the firm. The pecking order theory were tested when the management behaviortended to retained earnings in accumulating sources of the fund equity rather than borrowing liabilities fromcreditors. Therefore, rationally if the capital structure was optimum, management tended to external financinguntil any trade off between earnings and debt financing. Based on the testing hypothesis, it indicated that therole of capital structure dimension had significance as intervening variable between earnings dimension andfirms value. On the other hand, the dividend policy had no significance to become intervening variable.Empirically, it could be concluded that the management behavior in Indonesia tended to leverage rather thanretained earnings accumulation in supporting the pecking order theory. Furthermore, the variable had the roleto differentiate the characteristic of industries represented by the capital structure dimension, especially, debtto assets and debt to equity ratio.